Pak2 as a Novel Therapeutic Target for Cardioprotective Endoplasmic Reticulum Stress Response. Issue 5 (1st March 2019) - Binder, Pablo; Wang, Shunyao; Radu, Maria; Zin, Min; Collins, Lucy; Khan, Saba; Li, Yatong; Sekeres, Karolina; Humphreys, Neil; Swanton, Eileithyia; Reid, Adam; Pu, Fay; et al.
Abstract : Rationale: : Secreted and membrane-bound proteins, which account for 1/3 of all proteins, play critical roles in heart health and disease. The endoplasmic reticulum (ER) is the site for synthesis, folding, and quality control of these proteins. Loss of ER homeostasis and function underlies the pathogenesis of many forms of heart disease. Objective: : To investigate mechanisms responsible for regulating cardiac ER function, and to explore therapeutic potentials of strengthening ER function to treat heart disease. Methods and Results: : Screening a range of signaling molecules led to the discovery that Pak (p21-activated kinase)2 is a stress-responsive kinase localized in close proximity to the ER membrane in cardiomyocytes. We found that Pak2 cardiac deleted mice (Pak2-CKO) under tunicamycin stress or pressure overload manifested a defective ER response, cardiac dysfunction, and profound cell death. Small chemical chaperone tauroursodeoxycholic acid treatment of Pak2-CKO mice substantiated that Pak2 loss-induced cardiac damage is an ER-dependent pathology. Gene array analysis prompted a detailed mechanistic study, which revealed that Pak2 regulation of protective ER function was via the IRE (inositol-requiring enzyme)-1/XBP (X-box–binding protein)-1–dependent pathway. We further discovered that this regulation was conferred by Pak2 inhibition of PP2A (protein phosphatase 2A) activity. Moreover, IRE-1 activator, Quercetin, and adeno-associated virus serotype-9–delivered XBP-1s were able to relieve ER dysfunction in Pak2-CKO hearts. This provides functional evidence, which supports the mechanism underlying Pak2 regulation of IRE-1/XBP-1s signaling. Therapeutically, inducing Pak2 activation by genetic overexpression or adeno-associated virus serotype-9–based gene delivery was capable of strengthening ER function, improving cardiac performance, and diminishing apoptosis, thus protecting the heart from failure. Conclusions: : Our findings uncover a new cardioprotective mechanism, which promotes a protective ER stress response via the modulation of Pak2. This novel therapeutic strategy may present as a promising option for treating cardiac disease and heart failure. Abstract : Supplemental Digital Content is available in the text.